موارد العلامة المحدث عبد الحق الدهلوي في تفسير غريب الحديث من خلال كتابه "لمعات التنقيح في شرح مشكاة المصابيح" =The resources of al-Muhaddith Abd al-Haq al-Dahlawi in interpreting hadith difficult terms through his book: “Lama’at al-Tanqih fi sharh Mishkat al-Masabih” - Al-Nadwi, Fariduddin Fahimuddin; Mohammed Yaqub, Mohammed Abullais Shamsuddin (IIUM Press, 2020)
لقد حاول هذا البحث تسليط الضوء على جانب مهم في غريب الحديث، وتناول بيان موارد العلامة المحدث عبد الحق الدهلوي في تفسير الغريب في كتابه "لمعات التنقيح في شرح مشكاة المصابيح" باستخدام كل من المنهج الاستقرائي والتحليلي، كما تحدث عن أن الشارح شرح معنى الحديث بالآيات القرآنية والأحاديث النبوية، وكذلك بالموارد اللغوية، ثم بالشروح الحديثية، لأجل ذلك اختار البحث نماذج تطبيقية في كل ذلك، وخلص البحث إلى بيان أهمية كتاب "اللمعات" بين شروح المشكاة من حيث تعدد موارده خاصة في غريب الحديث، والتي أضفت على شرحه ميزة امتاز بها عن غيره، وكذا من حيث سعة اطلاعه وغزارة علمه ومعرفته بالآيات القرآنية والكتب الحديثية في الاستفادة والاستشهاد بها، ومن هنا ظهرت ضرورة العناية بأعمال الشيخ المحدث الدهلوي العلمية التي قام بها. ************************************* This research attempted to shed light on an important aspect of Ghrīb al-Hadīth,and further dealt with the sources of Ghrīb al-Hadīth as stated by the Sheikh ‘Abdal- Ḥaqq al-Muḥaddith al-Dehlawī in his book “Lam‘āt fi Sharḥ Mishkāt al-Maṣābīh”, employing both the inductive and analytical research methods. The research also discussed about what Muhaddith al- Dehlawī has explained regarding the meaning of Hadīth in the light of the verses of Holy Qur’an, Aḥādīth of Prophet (PBUH) linguistic resources and commentaries of Hadīth. That’s why, this research involved practical models in all of this. The research concluded expounding the importance of the book “Al-Lam‘āt” among the commentaries of Mishkāt in terms of the multiplicity of its resources as elucidated by al-Muḥaddith al- Dehlawī, particularly in Ghrīb al-Hadīth. This importance further appears in terms of his deep knowledge of the Quranic verses and books of Hadīth in benefiting from and arguing with them. At this point, the necessity of capitalizing the scientific work of Sheikh alMuḥaddithAl-Dehlawi is realized.